Emerging Resistance and Virulence Patterns in Salmonella enterica: Insights into Silver Nanoparticles as an Antimicrobial Strategy - Irina Gheorghe-Barbu; Ilda Czobor Barbu; Rareș-Ionuț Dragomir; Ioana Cristina Marinaș; Miruna Silvia Stan; Radu Pericleanu; Andreea Ștefania Dumbravă; Liviu-Iulian Rotaru; Simona Paraschiv; Leontina Mirela Bănică; Ionuț Pecete; Dan Oțelea; et al. (Antibiotics)
Background/Objectives: This study aims to characterize antibiotic resistance (AR) and virulence markers in Salmonella spp. isolated from Romanian outpatients’ stool samples. Methods: In 2019, community-acquired Salmonella strains were collected and identified using MALDI-TOF mass spectrometry, antibiotic susceptibility profiles have been determined with the MicroScan system, and soluble virulence factors were evaluated using specific culture media, while biofilm formation was quantified in 96-well plates. Molecular analysis targeted resistance genes for β-lactams (e.g., blaTEM and blaSHV); tetracyclines (e.g., tet(A)); sulphonamides; and quinolones, as well as virulence genes (e.g., invA, spvC, pldA, and held). Whole-genome sequencing (WGS) was performed on 19 selected isolates. A silver nanoparticles (AgNPsol) alternative to conventional antibiotics was tested for effectiveness against multidrug-resistant (MDR) isolates. Results: From the total of 309 Salmonella isolates (65.05% from children under 4 years of age) belonging to four subtypes and four serovars, 27.86% showed resistance to at least one antibiotic, most frequently to tetracycline, ampicillin, and piperacillin. The strains frequently expressed haemolysin (67%), aesculinase (65%), and gelatinase (62%). Resistance to trimethoprim-sulfamethoxazole was encoded by the sul1 gene in 44.83% of the strains and to tetracyclines by the tet(A) gene (59.52%). The ESBL genes blaTEM, blaSHV, and blaCTX-M were detected by PCR in 16.18%, 2.91%, and 0.65% of the strains, respectively. Additionally, 98.63% of the strains carried the invA marker, with notable positive associations between blaSHV, qnrB, and sul1 with spvC. Conclusions: The present findings revealed significant patterns in Salmonella isolates, subtypes, serovars, AR, and virulence, emphasising the need for continuous surveillance of Salmonella infections. Additionally, the potential of AgNPs as an alternative treatment option was demonstrated, particularly for paediatric S. enterica infections.